Predictors of Success for Stone Fragmentation and Stone-Free Rate After Extracorporeal Shockwave Lithotripsy in the Treatment of Upper Urinary Tract Stones - Takahara, Kiyoshi; Ibuki, Naokazu; Inamoto, Teruo; Nomi, Hayahito; Ubai, Takanobu; Azuma, Haruhito (Urology Journal, 2012)
PURPOSE: To evaluate factors affecting the success rate of stone fragmentation and stone-free rate after extracorporeal shockwave lithotripsy (SWL) in treatment of upper urinary tract stones. MATERIALS AND METHODS: A total of 121 patients with upper urinary tract calculi underwent SWL treatment. RESULTS: Success rate of stone fragmentation after SWL was 73.6% (89/121). In 89 patients who had success of breaking stones, 71 patients were followed up for the assessment of stone-free status, of whom 51 (71.8%) patients were stone-free at 3-month follow-up. Among four prognostic factors, including body mass index (BMI), stone size, stone position, and hydronephrosis, BMI and stone position had a significant impact on the success rate of stone fragmentation (P = .04 and U1: P = .0108, respectively). Among five prognostic factors of BMI, stone size, stone position, hydronephrosis, and times of SWL treatments, stone size was the only factor with significant impact on the stone-free rate (middle: P = .0229). CONCLUSION: Our study suggests that stone fragmentation and stone-free rate after SWL treatment for upper urinary tract stones can be predicted.